Music Composition: Kan Damnoen for Violin Trio - Sungwijit, Thaphad (Rangsit Music Journal, 2022)
The research article “Music Composition: Kan Damnoen for Violin Trio” approximately 10 minutes duration inspired by the composer’s everyday lives. It comprises of three pieces, the first piece: Pizzicato in the Morning, using the pizzicato technique, the second piece: In the Afternoon, using a pedal note with various rhythmic, the third piece: In the Evening using slur and staccato technique on eighth notes. The Composition was performed by virtual ensemble at Chiangmai Rajabhat University National Conference in September 9, 2021.